2004
DOI: 10.1007/s00467-004-1529-6
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler ultrasonography in the diagnosis of acute childhood pyelonephritis

Abstract: In the absence of specific symptomatology in children, the early diagnosis of acute pyelonephritis (APN) is a challenge, particularly during infancy. In an attempt to differentiate APN from lower urinary tract infection (UTI), we evaluated the ability of power Doppler ultrasonography (PDU) to predict renal parenchymal involvement, as assessed by dimercaptosuccinic acid ((99m )Tc-DMSA) scintigraphy. The study comprised 62 patients, 46 girls and 16 boys, aged 2 weeks to 5 years, admitted to the pediatric departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 31 publications
(37 reference statements)
3
25
0
14
Order By: Relevance
“…Another observation of us was that most of the false negative results of our patients were related with the left kidney. As emphasized in other studies, this can be explained with affection of the image quality of the blood flow in the upper pole of the left kidney because of lack of hepatic acoustic window of the left kidney (10,16,19).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Another observation of us was that most of the false negative results of our patients were related with the left kidney. As emphasized in other studies, this can be explained with affection of the image quality of the blood flow in the upper pole of the left kidney because of lack of hepatic acoustic window of the left kidney (10,16,19).…”
Section: Discussionmentioning
confidence: 79%
“…Eggli et al (18) were the first investigators who showed that the sensitivity of USG in detecting inflammation in renal perenchyma increased from 38% to 63% with As a result, they found the sensitivity and specificity values to be 92.1% and 93.8% for DMSA, 86.8% and 87.5% for CT, 89.50% and 87.5% for magnetic resonance imaging (MRI) and 74.3% and 56,7% for PDUS. After this study, more satisfactory results were published both for adult and pediatric patient groups (4,5,7,10). In fact, a marked advancement occured in the USG technology after the first studies which evaluated the success of this method and the sensitivity has been reported to be 74-89% in recent studies (19,20).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Multiple experimental and clinical studies compared the ability of different imaging modalities to diagnose upper UTI in the pediatric population [1,2,4,15,16,25]. Renal involvement and scarring has a multifactorial pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, early detection of renal involvement is essential for intensity and duration of treatment, as acute pyelonephritis (aPN) may result in irreversible renal damage. APN can induce renal scars as a complication; the importance of aPN-associated risks is under debate, but long-term complications such as hypertension and chronic renal failure have to be considered [2]. Therefore, an early, reliable, and accurate as well as easily accessible imaging method for aPN assessment may be valuable [3].…”
Section: Introductionmentioning
confidence: 99%